Інтеграція запорозької старшини до російської армії в кінці XVIII ст.: Клим Перепілін (за матеріалами РДВІА) - Краснобай, С. (Чорноморська минувшина, 2013)
У статті запропоновані документи з Російського державного військово- історичного архіву, за якими можна з’ясувати шлях отримання колишніми запорозькими старшинами офіцерських звань російської армії, а отже можливості отримання дворянства та зберегти провідне становище в суспільстві після зруйнування Запорозької Січі у 1775 р. Цей шлях показаний за прикладом комплексу документів полкового старшини Климента Перепіліна. На підставі останніх доведено, що надання офіцерського чину вимагало виконання певних доручень російської адміністрації, зокрема вербування колишніх козаків в іррегулярні формування Російської імперії (в тому числі у майбутнє Чорноморське козацьке військо). Виконання цих доручень вимагало тривалого терміну, що також свідчать репрезентовані документи. Having used archive materials and on the sample of regimental sergeant Kliment Perepilin, the author investigates the process of transformation of Zaporizhian elite into Russian army officers. Demolition of Zaporizhian Sich in 1775 and its further fate as one of the problems within the studies of Step Ukraine History is topical nowadays. Ukrainian historians put their utmost attention to this problem. Within this issue we can emphasize a number of articles and investigations which partially reveal the process and scale of Zaporizhian senior officers’ integration into Russian army officers’ body. This process was an integral part of Zaporizhian senior officers’ transformation into Russian empire nobles. But we must mention that such publications have only general character. The author chronologically lists quantitative composition of Zaporizhian elite which was awarded by the Russian government not taking into consideration individual conditions for every officer in this process. We suppose that regimental sergeant Kliment Perepilin’s inclusion into the officers’s body of the Russian army had been already made at the times Chornomorskiy Cossack army. Among the registers of this regular formation, we have come across the surname of Army Colonel second major Kliment Perepelytsya. We can guess that Kliment Perepilin and Kliment Perepelytsya is one and the same person. So, on the sample of regimental sergeant Kliment Perepilin we can trace conditions and peculiarities of Zaporizhian elite integration into Russian army officers’ body. Offered to the reader’s attention documents are published for the first time with all their language, grammar and stylistic mistakes. В статье предложены документы из Российского государственного военно- исторического архива, по которым можно определить путь получения бывшими запорожскими старшинами офицерских званий русской армии, а следовательно возможности получения дворянства и сохранения ведущего положение в обществе после разрушения Запорожской Сечи в 1775 г. Этот путь показан на примере комплекса документов полкового старшины Климента Перепилина. На основании последних доказано, что предоставление офицерского чина требовало выполнения определенных поручений российской администрации, в частности привлечения бывших казаков в иррегулярные формирования Российской империи (в том числе в будущее Черноморское казачье войско). Выполнение этих поручений требовало длительного времени, о чем также свидетельствуют представленные документы.